Load–response correlation–based equivalent static wind loads for large cooling towers. Issue 11 (August 2019) - Cao, SS; Ke, ST; Zhang, WM; Zhao, L; Ge, YJ; Cheng, XX
The load–response correlation method has been recognized by the wind engineering community as a useful equivalent static wind load calculation method for structural design of quasi-static structures against strong winds. However, it has been found that the load–response correlation method is less effective to non-linear systems and in situations where load processes are non-Gaussian, such as large cooling towers subjected to strong winds. To validate the applicability of the load–response correlation method to large cooling towers, an aero-elastic model has been designed for a 215-m-high cooling tower in this article, which can simultaneously produce wind loads and wind-induced displacements of the structure according to wind tunnel model tests. Using data measured on the aero-elastic model, the exact results of correlation coefficients between wind loads and structural responses are obtained and validated by a non-linear finite element analysis. By comparing the correlation coefficients measured on the scaled model to the results based on the load–response correlation calculation, it is found that the correlations are much stronger for the load–response correlation calculation than those for the exact wind tunnel measurement. The explanation for this observation is that the non-linearity of the real structure and the non-Gaussian feature of the actual wind loads can weaken the correlations between the wind loads and the structural responses.